2018
DOI: 10.1371/journal.pone.0203359
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitors reduce the accuracy of faecal immunochemical test for detecting advanced colorectal neoplasia in symptomatic patients

Abstract: BackgroundThe faecal immunochemical test (FIT) is used in colorectal cancer (CRC) screening and for the detection of advanced colorectal neoplasia (AN) in symptomatic patients, but its accuracy could be improved. Our objective was to assess the impact of proton pump inhibitors (PPI) on the accuracy of the FIT in the detection of AN, namely advanced colorectal adenoma and CRC.Methods and findingsWe performed a prospective study of 1002 individuals referred for a diagnostic colonoscopy at Bellvitge University Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Similarly, the effects of medications were not evaluated in the studies included for FIT meta-analysis. 49 These could have influenced the outcome of this review. Larger diagnostic accuracy studies evaluating sample media and optimising analytical methods are required.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the effects of medications were not evaluated in the studies included for FIT meta-analysis. 49 These could have influenced the outcome of this review. Larger diagnostic accuracy studies evaluating sample media and optimising analytical methods are required.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, in the study by Rodriguez-Alonso et al [17] logistic regression was performed for the false positive and false negative results at a cut-off level of 20 μg/g faeces. Since false positive and false negative rates are dependent on the cut-off value applied, the findings cannot be generalized to other cut-off levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although PPI exposure resulted in low precision estimates for the FIT, it did not reach a statistically significant level in predicting the outcome – whether CRC from other conditions (all adenoma, other bowel conditions or normal) or advanced neoplasia from other conditions (nonadvanced adenoma, other bowel conditions or normal). A previous study by Rodriguez‐Alonso et al [17] looked at the effect of PPI therapy on performance of the FIT for the detection of CRC and advanced neoplasia. This study showed there was no significant difference between the precision estimates in PPI and non‐PPI groups for the detection of CRC, which was similar to our findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations